1995
DOI: 10.1002/pro.5560041109
|View full text |Cite
|
Sign up to set email alerts
|

Two steps in the transition between the native and acid states of bovine α‐lactalbumin detected by circular polarization of luminescence: Evidence for a premolten globule state?

Abstract: A few studies indirectly support the existence of an intermediate in the transition of Ca2+-saturated bovine a-lactalbumin (a-LA) from the native (N) to the acidic (A) state, known as the molten globule state. However, direct experimental evidence for the appearance of this intermediate has not been obtained. The signal of circular polarization of luminescence (CPL) is sensitive to fine conformational transitions because of its susceptibility to changes in the environmental asymmetry of fluorescent chromophore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…bLA is a useful model for studies of protein folding because of its lower cooperativity, reflected in alternative conformations in different crystal forms (24), its equilibrium stable MG state, and the unique structure of its apo-form revealed here. A pre-MG state that is stable at equilibrium under mildly acidic conditions has been also described (53,54), suggesting that additional near-native partially unfolded conformations may be accessible to structural analysis. Studies are in progress to determine if apo-bLA can be crystallized under more destabilizing conditions to allow the structural analysis of other conformers that illuminate additional steps in the unfolding process.…”
Section: Resultsmentioning
confidence: 93%
“…bLA is a useful model for studies of protein folding because of its lower cooperativity, reflected in alternative conformations in different crystal forms (24), its equilibrium stable MG state, and the unique structure of its apo-form revealed here. A pre-MG state that is stable at equilibrium under mildly acidic conditions has been also described (53,54), suggesting that additional near-native partially unfolded conformations may be accessible to structural analysis. Studies are in progress to determine if apo-bLA can be crystallized under more destabilizing conditions to allow the structural analysis of other conformers that illuminate additional steps in the unfolding process.…”
Section: Resultsmentioning
confidence: 93%
“…Interestingly, it has been found that some associative forms of α-LA can induce apoptosis in tumor cells [356,357]. αLA is known to adopt different partially folded conformations under mildly denaturing conditions [353][354][355][358][359][360]. In addition, disulfide bridges were shown to play a very important role in the stabilization of α-LA structure [361][362][363][364][365].…”
Section: Carboxymethylated α-Lactabuminmentioning
confidence: 99%
“…Like most denatured or partially denatured state of proteins (30,31), it comprises a large number of conformational isomers. So far, characterization of the structure of denatured ␣-LA and the molten globule state of ␣-LA have been achieved by measuring the average property of these collective isomers using a wide range of spectroscopic and physiochemical methods, including circular dichroism (1,2,19,32), fluorescence (12,32,33), NMR (5,14,15,20,29,34), disulfide replacement (35)(36)(37), limited proteolysis (38,39), light scattering (40,41), and calorimetric techniques (42). Further understanding of the denatured state of ␣-LA and the molten globule state of ␣-LA will require fractionation of diverse populations of conformational isomers that constitute the denatured ␣-LA.…”
Section: ␣-Lamentioning
confidence: 99%